Free Speech and Expression - Merino, Noël, editor 522928; Gale Group (Online service) 651863 (Detroit, MI : Greenhaven Press, 2012)
Examines a broad range of perceived or actual legal rights and freedoms that impact the lives of young American teens. This volumes focus is on free speech and expression.